UVA-induced loss of quinolone antibacterial activity - FERNÁNDEZ, E; SÁNCHEZ, G; NAVARRETE, E; DEL ALCÁZAR, F (Ars Pharmaceutica (Internet), 2004)
The antibacterial activity of UVA-irradiated solutions of nalidixic acid, ciprofloxacin and levofloxacin was investigated.Photolysis of quinolones produced a decrease in antibacterial activity in strains of E. coli and S. aureus, becomingmanifest through an increase of 50% in the minimum inhibitory concentration of the drug as compared to nonirradiatedquinolones. In this study, it is suggested that a radical-mediated photolytic mechanism exists, leading to thephotodegradation of the γ-piridone-β-carboxylic group, which is the mediator that is responsible for the drugs antibacterialactivity